Processing Technologies for Bee Products: An Overview of Recent Developments and Perspectives - Luo, Xuan; Dong, Yating; Gu, Chen; Zhang, Xueli; Ma, Haile (Frontiers in Nutrition, 2021)
Abstract Backgroud: Greatly demand for a more balanced, healthy and safe diet have triggered the acceleration of the studies on the natural bee products (honey, royal jelly, propolis, bees wax, bee pollen, bee venom, bee bread etc.) over the past decade. Efficient processing technologies are greatly needed. Advanced food processing technologies like US, microwave, IR etc. have experienced increased popularity as alternatives or combined with the conventional processing methods for diverse applications in the apicultural products at a laboratory or an industrial scale. Scope and approach: This paper reviews firstly give the knowledge about the history of the bee products and the basic nutitional compounds in each. Then the processsing techologies of each bee products are comprehensive summrized such as drying (traditional, IR, MA, MW-VD, LTHV et al.) and store, extraction, isolation and identification, assessment methods related with the quality control of the bee products also fully mentioned. In paticular, the related equipments were also showed comprehensively. Key findings and conclusions: In general, history of apitherapy and hive products dates back to the old times, the obvious healing propertise and nutritional value are associated with the carbohydarte, protein, peptide, fatty acid and even phenolic and flavonoid compounds in it. The different processsing techologies used in the bee products are aims to largely and effecient obtain more healthy compounds. In addition, realise shorter processing time, reduced operational cost and improved product quality are achieved by using the conventional or emerging processing technoligies. It is hoped that this review paper will increase positive ratings of the combined newly processing technologies according to the need of the bee products. However, besides the newly design processing technologies and equipements for more good quality bee products, it is important that the models for the process optimization at the large scale also should be put more emphasis in the futuer.